2020
DOI: 10.1016/j.biteb.2020.100491
|View full text |Cite
|
Sign up to set email alerts
|

Indirect implications of COVID-19 towards sustainable environment: An investigation in Indian context

Abstract: Efficacious transmittal of COVID-19 has compelled numerous countries worldwide to embrace temporary yet dramatic measures such as locking down entire cities, restricting all forms of transportation, imposing lockdowns, maintaining social distancing etc. These actions have considerably enhanced the quality of ambient air and water. India, being a densely populated country, imposed a strict nationwide lockdown mandate since the last week of March 2020. This paper discusses the effects of COVID-19 restrictions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
165
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(182 citation statements)
references
References 12 publications
4
165
0
7
Order By: Relevance
“…It is found that, among the 36 real-time monitoring stations of river Ganga, water from 27 stations met the permissible limit (Singhal and Matto, 2020). This improvement of water quality at Haridwar and Rishikesh was ascribed to the sudden drop of the number of visitors and 500% reduction of sewage and industrial effluents (Singhal and Matto, 2020;Somani et al, 2020). According to the real-time water quality monitoring data of the Uttarakhand Pollution Control Board (UPCB, 2020) of India, physicochemical parameters i.e, pH (7.4-7.8), dissolved oxygen (DO) (9.4-10.6 mg/L), biochemical oxygen demand (BOD) (0.6-1.2 mg/L) and total coliform (40-90 MPN/100 mL) of the river Ganga was found within the surface water quality standard of India.…”
Section: Reduction Of Water Pollutionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is found that, among the 36 real-time monitoring stations of river Ganga, water from 27 stations met the permissible limit (Singhal and Matto, 2020). This improvement of water quality at Haridwar and Rishikesh was ascribed to the sudden drop of the number of visitors and 500% reduction of sewage and industrial effluents (Singhal and Matto, 2020;Somani et al, 2020). According to the real-time water quality monitoring data of the Uttarakhand Pollution Control Board (UPCB, 2020) of India, physicochemical parameters i.e, pH (7.4-7.8), dissolved oxygen (DO) (9.4-10.6 mg/L), biochemical oxygen demand (BOD) (0.6-1.2 mg/L) and total coliform (40-90 MPN/100 mL) of the river Ganga was found within the surface water quality standard of India.…”
Section: Reduction Of Water Pollutionmentioning
confidence: 99%
“…Since the outbreak of COVID-19, medical waste generation is increased globally, which is a major threat to public health and environment. For sample collection of the suspected COVID-19 patients, diagnosis, treatment of huge number of patients, and disinfection purpose lots of infectious and biomedical wastes are generated from hospitals (Somani et al, 2020;Zambrano-Monserrate et al, 2020). For instance, Wuhan in China produced more than 240 metric tons of medical wastes every day during the time of the outbreak (Saadat et al, 2020), which is almost 190 m tonnes higher than the normal time (Zambrano-Monserrate et al, 2020).…”
Section: Increase Of Biomedical Waste Generationmentioning
confidence: 99%
See 3 more Smart Citations